Hypothalamic–pituitary–adrenal dynamics in early-stage COVID-19 observed in a case with arginine vasopressin deficiency - Hinako Kirikae; Yuta Tezuka; Michiko Okamoto; Ginji Furuta; Kei Omata; Yoshikiyo Ono; Tetsuhiro Tanaka; Fumitoshi Satoh (BMC Endocrine Disorders)
Abstract Background The impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on pituitary function remains unclear, particularly during the acute phase of coronavirus disease 2019 (COVID-19). Case presentation We report the case of a 40-year-old man with arginine vasopressin deficiency (central diabetes insipidus) who was admitted for the evaluation of anterior pituitary function. The patient developed mild COVID-19 during the hospitalization, when we inadvertently observed rapid activation of the hypothalamic–pituitary–adrenal (HPA) axis prior to the onset of fever. At the estimated onset of COVID-19, the patient’s body temperature and the serum level of C-reactive protein remained within normal limits, whereas plasma ACTH levels drastically elevated, and subsequently, serum cortisol levels remain consistently high throughout the day, resulting in increased urinary free cortisol. The serum levels of several cytokines, including IFN-γ, IL-1RA, IL-6, and TNF-α, were also significantly elevated compared to those in the non-infected state. Acute suppression of thyroid and gonadal functions was observed approximately one day after the HPA axis activation. Conclusions These findings illustrate the rapid response of the HPA axis to inflammatory factors in the early-stage COVID-19, which may have important implications for understanding the initial host responses to SARS-CoV-2 infection.